Peculiarities of a riddle genre in Karachay-Balkarian folklore - Zhauhar M. Lokyaeva (Кавказология)
This article is devoted to revealing the traits of origin, development, existence of riddle as a genre of Karachay-Balkarian folklore, identification of its principal specific features. It is observed that, having arisen based on sacred texts in a secret language, subsequently it transformed and gained a game form. At present, the game (ritual) part has lost its significance because of changes that have occurred in the way of life of the native people, and riddles functioned in a question–answer format. The addressee of riddles has also changed: if earlier they were mostly used by adults during game competitions, then today riddles are often ranked among children’s genres of folklore, contributing to intergenerational transmission of information. The conducted research allows to state the existence of a close connection between the content of riddles and realities that surrounded their creators (geographical landscape, the world of flora and fauna, the material and spiritual culture of the ethnic group). All this determined the range of the thematic scope of Karachay-Balkarian riddles and therefore increased their research potential both for specialists in folklore and for linguists, ethnologists, culturologists and ethnopsychologists. In addition, the attention of the works of this genre on the development of abstract, figurative thinking, fantasy actualizes the possibility of their use for pedagogical purposes.